Sound Technology and the Naturalization of Sounds in the Peruvian Huayno (Revista Argentina de Musicología, 2012)
In this text I suggest that sound technology the recording techniques played an important role in the formation of the Peruvian huayno since the second half of the 20th Century. The article discuss the strategies of naturalization of media undertaken by Andean musicians in order to represent themselves as advocates of an old tradition and not as modern-oriented artists. Special attention is paid to the work of the composer and singer Luis Ayvar, from Ocobamba, who uses digital techniques to produce very “traditional” huaynos. The research is based on an ethnographic experience of “participant listening” which I have been conducting since 2002 in Luis Ayvar’s recordings sessions.
Keywords: huayno; Andean Music; sound technology; recording techniques and media